Biochemisry laboratory - Strong,F. M.; Biomedical Interdisciplinary Curriculum Project, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
Designed to accompany the student text on respiration, this manual presents instructions on the use of laboratory equipment and presents various experiments dealing with the concepts presented in the text. Thirty-nine laboratory activities are described. Laboratory activities are divided into several parts, each part covering a specific experiment dealing with the concept covered by the activity. Each experiment includes a description of materials, procedures, and discussion questions. (RE)
Sponsoring Agency: National Science Foundation, Washington, DC.
ERIC Note: For related documents, see SE 027 978-999 and SE 028 510-516; Not available in hard copy due to copyright restrictions.
Educational level discussed: Higher Education.
Educational level discussed: Secondary Education.
Microfiche.
Keywords: Chemistry; Environment; Health; Health Education; Higher Education; Laboratory Experiments; Laboratory Manuals; Laboratory Techniques; Laboratory Training; Medical Education; Pathology; Physics; Physiology; Science Education; Secondary Education; Respiration; Guides, Classroom -- Learner